2012
DOI: 10.1590/s0100-69162012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da velocidade e da direção do vento na uniformidade de aplicação de água de sistemas autopropelidos

Abstract: RESUMO:A velocidade e a direção de incidência do vento, em relação ao eixo de deslocamento do aspersor, são variáveis apresentadas em vários trabalhos como fatores importantes para a determinação da uniformidade de aplicação de água dos equipamentos autopropelidos de irrigação. No entanto, em razão das dificuldades de se conduzir estudos de campo com canhões hidráulicos sob condições controladas de direção e velocidade do vento, as recomendações de espaçamento entre carreadores, em sua maioria, consideram apen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Therefore, well designed irrigation systems, with good uniformity of water application and proper irrigation management, provide higher yield, reduce water loss (Prado & Colombo 2011;Oliveira et al, 2012) and leaching (Agostinho, 2011), and maximize available water resources (Santos et al, 2013). For this reason, we need the right combination of the several factors which enable the quantification of water to be applied in each irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, well designed irrigation systems, with good uniformity of water application and proper irrigation management, provide higher yield, reduce water loss (Prado & Colombo 2011;Oliveira et al, 2012) and leaching (Agostinho, 2011), and maximize available water resources (Santos et al, 2013). For this reason, we need the right combination of the several factors which enable the quantification of water to be applied in each irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of most agro meteorological conditions, especially wind speed, among the experiments performed with the two types of sprinklers are important data for the analysis of the distribution of the water depth during irrigation. Research by Justi et al (2010), , and Oliveira et al (2012) report that higher wind velocit ies can affect water jets as well as their direction, providing distortions regarding the uniformity of water distribution in the soil.…”
Section: Analysis Of the Agrometeorological Vari Ablesmentioning
confidence: 99%
“…The water distribution of a gun sprinkler, which works in a traveler irrigation machine, is influenced by controllable factors (sprinkler type, nozzle diameter, working pressure, jet angle, wetted angle, and space between strips) and weather factors (wind speed and direction) (Oliveira et al, 2012). Silva et al (2007) reported that traveling gun irrigation systems working with a large gun sprinkler are characterized as having low water application uniformity, especially in windy conditions.…”
Section: Introductionmentioning
confidence: 99%